Sleep Quality and Quality of Life in Remitted Bipolar Disorder Patients: A Cross-sectional Comparative Study - Kartik K Vangal; Savitha Soman; Rajeshkrishna P Bhandary; Samir Kumar Praharaj (Indian Journal of Psychological Medicine)
Background: Patients diagnosed with bipolar disorder often have sleep-related problems, even when not in an episode. Poor sleep quality may be related to poor quality of life. The objective of this study was to evaluate sleep quality in remitted bipolar patients and compare it to controls, as well as to study the relationship between quality of sleep and quality of life in euthymic bipolar individuals. Methods: We studied sleep quality and quality of life in 86 remitted bipolar disorder patients and 86 matched healthy controls using the Pittsburgh Sleep Quality Index (PSQI) and World Health Organization Quality of Life Assessment (WHOQOL-BREF). Results: There was significantly poorer sleep quality in euthymic bipolar patients compared to controls, especially in subjective sleep quality and sleep duration. WHOQOL-BREF domain scores were lower among patients than controls, with a large effect size. All domains on the PSQI correlated negatively with the domains on the WHOQOL-BREF, with the physical health domain being affected the most. Lack of generalizability of the results and the cross-sectional design that cannot determine causality are the limitations of our study. Conclusions: Poor sleep quality persists in bipolar patients even in the euthymic phase and correlates with a poor quality of life.